2020
DOI: 10.1210/clinem/dgaa750
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and its Determinants in Patients With Treated Acromegaly: A Cross-Sectional Nationwide Study in China

Abstract: Context Quality of life (QoL) continues to be impaired in acromegaly after treatment. Objective We conducted the first nationwide survey assessing QoL status among Chinese patients with treated acromegaly and explored correlations with clinical parameters, treatment modalities and outcomes. Design Cross-sectional study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…In this study, we showed that the factors associated with impaired AcroQoL were significantly different for various age groups. For young and middle-aged patients, treatment modalities including current medical therapy and past radiotherapy impaired the QoL score, as shown in previous reports ( 13 , 14 ). In contrast, treatment modalities did not affect the AcroQoL of older patients.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In this study, we showed that the factors associated with impaired AcroQoL were significantly different for various age groups. For young and middle-aged patients, treatment modalities including current medical therapy and past radiotherapy impaired the QoL score, as shown in previous reports ( 13 , 14 ). In contrast, treatment modalities did not affect the AcroQoL of older patients.…”
Section: Discussionsupporting
confidence: 80%
“…In a study of a healthy population using Short From-36 (SF-36), a widely used general health-related QoL questionnaire, QoL declined with age as a result of declines in physical, mental, and social functions ( 12 ). In a study using the AcroQoL questionnaire, a disease-specific questionnaire for acromegaly, some factors, including therapeutic modalities such as radiotherapy and drug therapy, symptoms such as headache and joint pain, and poor body image, contributed to poor QoL scores ( 13 , 14 ). We have previously developed a Japanese version of AcroQoL and showed that acromegaly patients with surgical remission have better QoL scores than young and middle-aged patients receiving medical treatment or radiotherapy ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that, combining the findings of the literature and clinical experience (Tiemensma et al, 2010;Zimmermann et al, 2018;Wolters et al, 2020;Guo et al, 2021), we also hypothesized at the beginning of the study that there was a correlation patients ' between hormone levels and psychology. However, only PRL, ACTH, and postoperative growth hormone levels were statistically significant in the univariate analysis, and the results of multiple linear regression showed no association between hormone levels and psychology.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the findings implied that the substantial adverse outcomes of elevated GH levels at diagnosis and subsequent endocrine-metabolic (except diabetes), musculoskeletal and cardiovascular comorbidities were associated with diagnostic delay. The increased comorbidities may reduce quality of life of the patients ( 27 ) and increase their mortality ( 28 , 29 ). This result is similar to the findings from the study using Swedish registry data ( 9 ) that patients with longer diagnostic delay tended to have more musculoskeletal, endocrine-metabolic and cardiovascular comorbidities in univariate analysis, while the pattern of respiratory disease prevalence across different length of diagnostic delay was unclear.…”
Section: Discussionmentioning
confidence: 99%